Lesions of the paraventricular nucleus of the thalamus differentially affect sign- and goal-tracking conditioned responses - Haight, Joshua L. (Eur J Neurosci, 2015)
Recently evidence has emerged suggesting a role for the paraventricular nucleus of the thalamus (PVT) in the processing of reward-associated cues. However, the specific role of the PVT in these processes has yet to be elucidated. Here we use an animal model that captures individual variation in response to discrete reward-associated cues to further assess the role of the PVT in stimulus-reward learning. When rats are exposed to a Pavlovian conditioning paradigm, wherein a discrete cue predicts food reward, two distinct conditioned responses emerge. Some rats, termed sign-trackers, approach and manipulate the cue; whereas others, termed goal-trackers, approach the location of reward delivery upon cue presentation. For both sign- and goal-trackers the cue is a predictor; but only for sign-trackers is it also an incentive stimulus. We investigated the role of the PVT in the acquisition and expression of these conditioned responses using an excitotoxic lesion. Results indicate that PVT lesions prior to acquisition amplify the differences between phenotypes—increasing sign-tracking and attenuating goal-tracking behavior. Lesions of the PVT after rats had acquired their respective conditioned responses also attenuated the expression of the goal-tracking response, and increased the sign-tracking response, but did so selectively in goal-trackers. These results suggest that the PVT acts to suppress the attribution of incentive salience to reward cues, as disruption of the functional activity within this structure enhances the tendency to sign-track.